Investigating the relationship between cognitions, pacing strategies and performance in 16.1 km cycling time trials using a think aloud protocol. (January 2018) - Whitehead, Amy E.; Jones, Hollie S.; Williams, Emily L.; Rowley, Chris; Quayle, Laura; Marchant, David; Polman, Remco C.
Abstract: Objectives: Three studies involved the investigation of concurrent cognitive processes and pacing behaviour during a 16.1 km cycling time trial (TT) using a novel Think Aloud (TA) protocol. Study 1 examined trained cyclist's cognitions over time whilst performing a real-life 16.1 km time trial (TT), using TA protocol. Study 2, included both trained and untrained participants who performed a 16.1 km TT in a laboratory whilst using TA. Study 3 investigated participants' experiences of using TA during a TT performance. Method: Study 1 involved 10 trained cyclists performing a real life 16.1 km TT. Study 2 included 10 trained and 10 untrained participants who performed a laboratory-based 16.1 km TT. In both studies, all participants were asked to TA. Time, power output, speed and heart rate were measured. Verbalisations were coded into the following themes (i) internal sensory monitoring, (ii) active self-regulation, (iii) outward monitoring (iv) distraction. Cognitions and pacing strategies were compared between groups and across the duration of the TT. In study 3 all participants were interviewed post TT to explore perceptions of using TA. Results: Study 1 and 2 found cognitions and pacing changed throughout the TT. Active self-regulation was verbalised most frequently. Differences were found between laboratory and field verbalisations and trained and untrained participants. Study 3 provided support for the use of TA in endurance research. Recommendations were provided for future application. Conclusion: Through the use of TA this study has been able to contribute to the pacing and cycling literature and to the understanding of endurance athletes' cognitions. Highlights: The Think Aloud protocol is a viable tool for collecting in-event cognitions during endurance exercise. Cognitive processes change throughout cycling time trials in both laboratory and field-based settings. Expertise influences thought processes and cognitive strategies during cycling performance. Future research should consider using the Think Aloud protocol to further explore the cognitions underpinning pacing behaviour in endurance performance.